The teachers eaudiobook A year inside america's most vulnerable, important profession. - Robbins, Alexandra (Books on Tape, 2023)
A National Bestseller *Winner of the 2024 DKG International Educators Book Award* A riveting, must-read, year-in-the-life account of three teachers, combined with reporting that reveals what’s really going on behind school doors, by New York Times bestselling author and education expert Alexandra Robbins. Alexandra Robbins goes behind the scenes to tell the true, sometimes shocking, always inspirational stories of three teachers as they navigate a year in the classroom. She follows Penny, a southern middle school math teacher who grappled with a toxic staff clique at the big school in a small town; Miguel, a special ed teacher in the western United States who fought for his students both as an educator and as an activist; and Rebecca, an East Coast elementary school teacher who struggled to schedule and define a life outside of school. Robbins also interviewed hundreds of other teachers nationwide who share their secrets, dramas, and joys. Interspersed among the teachers’ stories—a seeming scandal, a fourth-grade whodunit, and teacher confessions—are hard-hitting essays featuring cutting-edge reporting on the biggest issues facing teachers today, such as school violence; outrageous parent behavior; inadequate support, staffing, and resources coupled with unrealistic mounting demands; the “myth” of teacher burnout; the COVID-19 pandemic; and ways all of us can help the professionals who are central both to the lives of our children and the heart of our communities.